The Symbolic and Propaganda Message of the Heraldic Programmes in Two 17th-Century Marriage Prints (Epithalamia) of the Pacas Family - Czyż, Anna Sylwia (Knygotyra, 2020)
This article presents two printed epithalamia from the 17th c. related to marriages contracted in the Pacas family. Each of them was adorned with a graphic decoration conforming with the allegoric meaning of the Gozdawa coat-of-arms. This determined not only individual virtues but also, together with the relevant quotations and symbols, became a prognostic of a satisfactory marital life. It also demonstrated the connections of the Pacas family, which were crucial in terms of strengthening the position of both the family and its individuals against public and family issues.
Keywords: Pacas; epithalamium; stemmata; coat of arms; Gozdawa